2015
DOI: 10.1097/brs.0000000000000690
|View full text |Cite
|
Sign up to set email alerts
|

Infection Rate After Minimally Invasive Noninstrumented Spinal Surgery Based on 4350 Procedures

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 18 publications
2
23
0
5
Order By: Relevance
“…Data in the present study are consistent with those in previous reports evaluating minimally invasive techniques. 20,26,28,38 In a retrospective study using an administrative database, McGirt and colleagues 20 reported that their minimally invasive technique was associated with a decrease in the incidence of SSI following 2-level posterior/transforaminal lumbar interbody fusion. O'Toole and colleagues postulated several possible reasons for the lower risk of SSI associated with minimally invasive surgery: reduced exposure of deep tissue, preventive effect of a tubular retractor for local contamination, smaller incisions, and reduced dead space in the surgical site after closure.…”
Section: Discussionmentioning
confidence: 99%
“…Data in the present study are consistent with those in previous reports evaluating minimally invasive techniques. 20,26,28,38 In a retrospective study using an administrative database, McGirt and colleagues 20 reported that their minimally invasive technique was associated with a decrease in the incidence of SSI following 2-level posterior/transforaminal lumbar interbody fusion. O'Toole and colleagues postulated several possible reasons for the lower risk of SSI associated with minimally invasive surgery: reduced exposure of deep tissue, preventive effect of a tubular retractor for local contamination, smaller incisions, and reduced dead space in the surgical site after closure.…”
Section: Discussionmentioning
confidence: 99%
“…36 For instance, overall infection rates in noninstrumented minimally invasive spine surgeries are markedly reduced, 0.09%, compared with the incidence in the present analysis. 37 Additionally, complication rates will vary based on the type of procedure and medical indication.…”
Section: Discussionmentioning
confidence: 99%
“…[28] In this report series, Klebsiella pneumonia infection developed de novo post operative without gastrourinary trauma/associated infection per se thus was worth reporting. The infection rates after MISS the reported rates are 0.09% to 1% [29,30,31] . Concerns regarding the challenges a surgeon faces during initial experience with these systems.…”
Section: Discussionmentioning
confidence: 98%